Spatial assessment of climate change vulnerability at city scale: A study in Bangalore, India - Kumar, Parveen; Geneletti, Davide; Nagendra, Harini (Land use policy, 2016)
•Presents a methodological approach to assess vulnerability patterns to climate change at the local level based on three key components: exposure, sensitivity and adaptive capacity.•Assesses the spatial pattern of the vulnerability of an urban system in a semi-arid inland city in India.•Presents an approach to prioritise adaptation and mitigation response action within the spatial planning process.•91% of the total area of Bangalore metropolitan area is subject to a high degree of climate change vulnerability. Integrating adaptation and mitigation response actions to climate change in urban-level policies requires comprehensive information on vulnerability patterns, yet a majority of local governments and decision makers in various cities in developing nations lack spatially explicit information on climate change vulnerability and its key drivers. In addition, there is no standardised method for an all-inclusive vulnerability assessment at the local level. Results from higher broad-scale vulnerability assessments are difficult to implement conceptually and technically at the local scale. We present a climate change vulnerability assessment approach at the city scale that considers three main components: exposure, sensitivity and adaptive capacity. Indicators were assessed within each component and were combined using Spatial Multi-Criteria Evaluation (SMCE). The standardisation of indicators under each component was conducted, along with weighting, at each level of the vulnerability assessment hierarchy. The vulnerability assessment approach was applied to an urban area in India; namely, Bangalore metropolitan area. The application of vulnerability assessment approach was demonstrated and a spatial assessment of climate change vulnerability patterns was presented. The spatial pattern of vulnerability identifies areas urgently requiring attention to adaptation action, while vulnerability assessment enables policy intervention and prioritization at local spatial scales. This study presents a rational to integrate vulnerability assessment approach within the urban planning realm in Bangalore metropolitan area where according to our study approximately 91% of the area is facing high degree of climate vulnerability.